Difficulties in Developing Idea Encountered by Students in Writing Argumentative Essay - Saprina, Cindy Mutiara; Rosyid, Abdul; Suryanti, Yanti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2021)
Writing is one of the most important skills that have to be mastered in the art of language learning. In the university level, EFL students have essay writing subject that requires them to write many types of essay, among those being the argumentative essay. In writing an essay, they need to be able to develop their own original ideas, despite the fact that some of them still consider this a difficult task. This research is aimed to highlight set of difficulties encountered by students that are assigned to develop ideas whilst writing argumentative essay. This research was conducted at Pakuan University and involved 23 students as participant of this study. Qualitative method and descriptive analysis are applied in conducting this research. To gain the research data, three research instruments were used, they are: documentation, questionnaire and interview. Documentation instrument was used to analyze students work of argumentative essay. The questionnaire was administered to all participants and the interview was conducted once for each student. This study reveals that the students still have some difficulties in constructing thesis statement, organizing paragraph, making writing coherent and combining ideas in correct sentences. Finally, the result of this research may urge the students to improve their writing skills and provide the teachers to explore more on teaching writing practices.